Cross-sectional online survey to determine the prevalence, knowledge, attitude and practice of tobacco cessation among governmental healthcare workers in Qatar - Ahmad AlMulla; Silva Kouyoumjian; Nour ElNakib (BMJ Open)
Objectives One effective approach of tobacco control is to encourage the role and the participation of healthcare workers in the prevention efforts against tobacco use. This study aimed to determine the prevalence of tobacco use among governmental healthcare workers in Qatar, to assess healthcare workers’ knowledge, attitude and practice of tobacco cessation and to predict factors associated with above average tobacco cessation practice scores.Design A cross-sectional survey study was conducted among healthcare workers working in Hamad Medical Corporation and Primary Healthcare Centres in Qatar using a self-administered online questionnaire in 2019.Setting Hamad Medical Corporation and Primary Healthcare Centres in Qatar.Participants Governmental healthcare workers aged 18 years and above (n=7214).Results The response rate of our online survey was 20.6% (7214/35 000). Of the 7214 healthcare workers, 16.3% (n=1178) were current tobacco users. In particular, the prevalence of tobacco use among physicians was 11.0%. Fifty-two per cent of healthcare workers (n=2338) attained an average knowledge score (12–17), 71.8% (n=3094) attained positive attitude scores (8–12) and 57.1% (n=3052) attained above average practice scores (12–26). Among the different professions, physicians were having the highest mean knowledge (15.3±4.7), attitude (9.4±1.9) and practice (13.7±6.1) scores. Multivariate analysis showed that having good knowledge (adjusted OR (AOR)=2.8; p<0.0001) and training (AOR=2.4; p<0.0001) were the strongest factors associated positively with above average tobacco cessation practice scores.Conclusions Healthcare workers in Qatar have a relatively similar prevalence of tobacco use than earlier studies with no significant increase. Investing more in training programmes for healthcare workers are needed to root out this negative behaviour and to increase their skills to assist users to quit.